2020
DOI: 10.1051/e3sconf/202015803001
|View full text |Cite
|
Sign up to set email alerts
|

Carbon footprint of an EUR-sized wooden and a plastic pallet

Abstract: Pallets are an essential element of existing logistics worldwide. Pallets are simple in structure, yet they can be made of different materials, in varying dimensions, and be marketed via alternative management systems. This paper examines a carbon footprint, an indicator of impact on climate change, of a widely used EUR-size (1200 mm × 800 mm) pallet made of wood or plastic using the data from previously published literature. The study is geographically representative of Finland, while time and technological r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Life cycle analysis (LCA) found wood to have a significant advantage over plastics in this application. Assuming incineration as the disposal method, the carbon footprint of a wood pallet was 0.34 kg of carbon dioxide equivalent (CO 2 -e) four times lower than that of a plastic unit [8]. A Finnish study [7] agreed with the finding, but found wood-plastic composites (WPC) to have even a lower carbon footprint relative to wood.…”
Section: Introductionmentioning
confidence: 87%
“…Life cycle analysis (LCA) found wood to have a significant advantage over plastics in this application. Assuming incineration as the disposal method, the carbon footprint of a wood pallet was 0.34 kg of carbon dioxide equivalent (CO 2 -e) four times lower than that of a plastic unit [8]. A Finnish study [7] agreed with the finding, but found wood-plastic composites (WPC) to have even a lower carbon footprint relative to wood.…”
Section: Introductionmentioning
confidence: 87%
“…Four works focus specifically on the impacts of packaging of different materials: [82] compares disposable wood pallets with reusable steel cradles through LCA, showing the advantages of this latter option. The comparison between plastic and wood pallets is performed in five LCA studies: [83,84] underline the lower environmental impacts related to wood pallets, while [85] points out that the results depend on the type of plastic and wood considered. The author of [1] focuses on the impacts during transportation and confirms the better performance of wood versus plastic.…”
Section: Supply Chainmentioning
confidence: 99%
“…However, in the case of wood, WDC production could also be beneficial owing to its specific properties, such as moisture and UV resistance, higher strength, lack of treatment needs, and production of complex geometrical forms. When considering the application of WDC in the production of wooden pallets, substantial benefits could be expected from the better durability of pallets made of WDC, assuming their performance is closer to that of plastic, rather than wooden, ones (Deviatkin and Horttanainen, 2020). However, use phase impacts are always case-specific, so making a PCF of WDC is beneficial to ensure the use of such data by LCA practitioners working on attributional or comparative LCAs of products made of WDC.…”
Section: Impact Of Usementioning
confidence: 99%